Growth accounting for the euro area: a structural approach - Tommaso Proietti; Alberto Musso (European Central Bank (ECB), 2007)
This paper is concerned with the estimation of euro area potential output growth and its decomposition according to the sources of growth. The growth accounting exercise is based on a multivariate structural time series model which combines the decomposition of total output according to the production function approach with price and wage equations that embody Phillips type relationships linking inflation and nominal wage dynamics to the output gap and cyclical unemployment, respectively. Assuming a Cobb-Douglas technology with constant returns to scale, potential output results from the combination of the trend levels of total factor productivity and factor inputs, capital and labour (hours worked), which is decomposed into labour intensity (average hours worked), the employment rate, the participation rate, and population of working age. The nominal variables (prices and wages) play an essential role in defining the trend levels of the components of potential output, as the latter should pose no inflationary pressures on prices and wages. The structural model is further extended to allow for the estimation of potential output growth and the decomposition according to the sources of growth at different horizons (long-run, medium run and short run); in particular, we propose and evaluate a model–based approach to the extraction of the low–pass component of potential output growth at different cutoff frequencies. The approach has two important advantages: the signal extraction filters have an automatic adaptation property at the boundaries of the sample period, so that the real time estimates do not suffer from what is often referred to as the ”end–of-sample bias”. Secondly, it is possible to assess the uncertainty of potential output growth estimates with different degrees of smoothness.
Keywords: C32; C51; E32; O47; 330; euro area; Low-pass filters; output gap; potential output; Production function approach; Unobserved Components; Produktionspotenzial; Cobb-Douglas-Produktionsfunktion; Eurozone; Theorie; EU-Staaten